1975
DOI: 10.1161/01.str.6.6.715
|View full text |Cite
|
Sign up to set email alerts
|

Lactate and Pyruvate Concentrations, and Acid-Base Balance of Cerebrospinal Fluid in Experimentally Induced Intracerebral and Subarachnoid Hemorrhage in Dogs

Abstract: Abstract• The effect of blood injected into either subarachnoid space or subcortical brain tissue upon lactate and pyruvate concentrations as well as acid-base balance of cerebrospinal fluid (CSF) was studied in the anesthetized dog.CSF lactate and lactate/pyruvate ratio (L/P ratio) increased progressively following the intracranial injection of blood and reached the maximum level at six hours after injection. These changes were significantly greater in animals with intracerebral hematoma than in those with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
2
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 19 publications
6
32
2
1
Order By: Relevance
“…Granholm 14 reported the similar results revealing a greater increase in in vivo production of lactate than in in vitro, but the L/P ratio was unchanged for the three-hour study. From our experience, 16 however, CSF lactate increased progressively with time following the intracisternal injection of blood in dogs, but also CSF L/P ratio started to increase at three hours after injection. Granholm 14 described no significant changes in lactate or pyruvate of the feline brain tissue for three hours after the intracisternal injection of blood cells.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Granholm 14 reported the similar results revealing a greater increase in in vivo production of lactate than in in vitro, but the L/P ratio was unchanged for the three-hour study. From our experience, 16 however, CSF lactate increased progressively with time following the intracisternal injection of blood in dogs, but also CSF L/P ratio started to increase at three hours after injection. Granholm 14 described no significant changes in lactate or pyruvate of the feline brain tissue for three hours after the intracisternal injection of blood cells.…”
mentioning
confidence: 62%
“…- 13 Our previous study, 5 as well as others, 24 have shown that an increase in CSF lactate was more pronounced in hemorrhagic cerebrovascular diseases than in ischemic strokes. It is probable that shed blood cells' metabolism per se in CSF produced lactate.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…All animals in this study were alert and moving about in a relatively normal fashion prior to each anesthesia suggesting that the arterial blood gases reflect acute changes related to anesthesia and not an equilibrium situation. Sugi, et al 22 found a small increase in L / P ratio in the CSF in dogs four hours after SAH which was not significantly different from three control animals until at least five hours after onset. Our results agree with their findings, but we believe that one cannot conclude, as these authors did, that this small increase in the L / P ratio, even if significant, is due to decreased cerebral blood flow, as it may just as well relate to a non-hypoxic lactacidosis mediated by a fall in the phosphate potential."…”
Section: M1mentioning
confidence: 88%
“…The internal jugular venous O 2 content of the patients with marked disturbances of consciousness following SAH tended to increase in this study, but this change was not consistent and could not be considered characteristic. T. Sugi et al 18 reported that an increase in CSF lactate with a concomitant rise in CSF lactate/pyruvate ratio is a useful indicator of brain tissue hypoxia, even when the CSF is hemorrhagic. It is well known that brain hypoxia induces the lactic acidosis and accelerating glycolysis.…”
Section: Discussionmentioning
confidence: 99%